StrategivPemasaran Penerbangan Konsep Low Cost Carrier (LCC) Dan Daya Persaingan Perusahaan di PT. Lion Air Cabang Banjarmasin - Dheslinski Zenidah (Jurnal Multidisiplin Madani, 2022)
This study aims to describe the flight strategy on flights that have the low-cost carrier concept and the theory of business competition in Lion Air, a representative of Banjarmasin. The research was conducted on September 1, 2021 to September 30, 2021 at PT. Lion Air Banjarmasin Branch by conducting this Data Collection Method in the form of Interviews, Observations/observations and Documentation of the General Manager of Lion Air, Lion Air employees and marketing sales at PT. Lion Air branch located in Banjarmasin. The results of this Marketing Strategy Research implemented by Lion Air Company Banjarmasin Branch is quite well monitored from the study of Porter's competitive data theory. Lion Air Company Banjarmasin Branch in the last year, has made very rapid progress in the number of customers, frequency of navigation and navigation routes, because through cheap ticket prices, prepared this will be more accessible to lower-middle customers.